The road to recovery : how and why economic policy must change - Smithers, Andrew (Chichester, West Sussex : John Wiley & Sons Ltd, 2013)
Argues that the neoclassical consensus governing global economic decision-making must be revised in order to avoid the next financial collapse. It argues that the current low interest rates and budget deficits have prevented the recession becoming a depression but that those policies cannot be continuously repeated and a new consensus for action must be found.
Includes bibliographical references (pages 263-268) and index.
oif 16/06/15
Loan
Keywords: Economic policy; Financial crises -- Prevention